The World Trade Organization: between the XXth century rules and XXIst century Trade Policy - Zelicovich, Julieta (2020)
International trade relations are going through a period of transformation. From the analysis of statistics and documents, a trend towards the configuration of a new foreign trade policy at a global level, with higher levels of protectionism and distortive use of subsidies, is identified in this work. This new configuration has caused renewed tensions in relations between States, raising the question regarding the type of strategic actions that its approach requires. It is argued that multilateralism continues to present the greatest strengths in the face of this type of problem. Hence, there is a role for the World Trade Organization, filling the gap that exists between the “international trade rules of the 20th century” and the “new trade policies of the 21st century”.